Splenic lymphoma with villous lymphocytes in two sisters. - Ribeiro, I (1992)
Splenic lymphoma with villous lymphocytes is a new entity characterised by the presence of atypical lymphocytes in the peripheral blood and bone marrow, and splenic infiltration in the white and red pulp. Cell membrane markers are those of a B mature cell, and no particular chromosomal abnormalities have been associated with this disease. A case of this rare lymphoma occurred in two sisters. Histological examination of splenic tissue was identical in both cases, with the same immunological surface markers, although the clinical and laboratory features were different. Karyotype analysis showed an abnormal pattern in one case; no environmental causative factor could be detected. Familial cases of other lymphoproliferative disorders have been reported, but no consistent common link has been found. It is suggested that further reports of this lymphoma, including cytogenetic and molecular studies, may provide a better understanding of the aetiology.